Context-specific modulation of cocaine-induced locomotor sensitization and ERK and CREB phosphorylation in the rat nucleus accumbens - Marin, Marcelo Tadeu [UNESP]; Berkow, Alexander; Golden, Sam A.; Koya, Eisuke; Planeta, Cleopatra da Silva [UNESP]; Hope, Bruce T. (Wiley-Blackwell, 2009)
Learned associations are hypothesized to develop between drug effects and contextual stimuli during repeated drug administration to produce context-specific sensitization that is expressed only in the drug-associated environment and not in a non-drug-paired environment. The neuroadaptations that mediate such context-specific behavior are largely unknown. We investigated context-specific modulation of cAMP-response element-binding protein (CREB) phosphorylation and that of four upstream kinases in the nucleus accumbens that phosphorylate CREB, including extracellular signal-regulated kinase (ERK), cAMP-dependent protein kinase, calcium/calmodulin-dependent kinase (CaMK) II and CaMKIV. Rats received seven once-daily injections of cocaine or saline in one of two distinct environments outside their home cages. Seven days later, test injections of cocaine or saline were administered in either the paired or the non-paired environment. CREB and ERK phosphorylation were assessed with immunohistochemistry, and phosphorylation of the remaining kinases, as well as of CREB and ERK, was assessed by western blotting. Repeated cocaine administration produced context-specific sensitized locomotor responses accompanied by context-specific enhancement of the number of cocaine-induced phosphoCREB-immunoreactive and phosphoERK-immunoreactive nuclei in a minority of neurons. In contrast, CREB and CaMKIV phosphorylation in nucleus accumbens homogenates were decreased by cocaine test injections. We have recently shown that a small number of cocaine-activated accumbens neurons mediate the learned association between cocaine effects and the drug administration environment to produce context-specific sensitization. Context-specific phosphorylation of ERK and CREB in the present study suggests that this signal transduction pathway is selectively activated in the same set of cocaine-activated accumbens neurons that mediate this learned association.
Keywords: calcium; calmodulin-dependent kinase; CaMK; kinase; neuroadaptation; PKA